2017
DOI: 10.1519/jsc.0000000000001562
|View full text |Cite
|
Sign up to set email alerts
|

Full Range of Motion Induces Greater Muscle Damage Than Partial Range of Motion in Elbow Flexion Exercise With Free Weights

Abstract: Baroni, BM, Pompermayer, MG, Cini, A, Peruzzolo, AS, Radaelli, R, Brusco, CM, and Pinto, RS. Full range of motion induces greater muscle damage than partial range of motion in elbow flexion exercise with free weights. J Strength Cond Res 31(8): 2223-2230, 2017-Load and range of motion (ROM) applied in resistance training (RT) affect the muscle damage magnitude and the recovery time-course. Because exercises performed with partial ROM allow a higher load compared with those with full ROM, this study investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Therefore, it is difficult to separate the effect of EIMD on muscle hypertrophy from the effect of the confounding factors. For instance, training at long muscle lengths (i.e., the stretched position) is not only associated with a greater magnitude of EIMD (11,115) but also possibly with increased muscle hypertrophy when compared with exercising with short muscle lengths, at least in some muscles (14, 107). However, this may not be due to EIMD but due to the larger force production at longer fascicle lengths (40).…”
Section: Evidence From Human Studies For Eimd As a Hypertrophy Stimulusmentioning
confidence: 99%
“…Therefore, it is difficult to separate the effect of EIMD on muscle hypertrophy from the effect of the confounding factors. For instance, training at long muscle lengths (i.e., the stretched position) is not only associated with a greater magnitude of EIMD (11,115) but also possibly with increased muscle hypertrophy when compared with exercising with short muscle lengths, at least in some muscles (14, 107). However, this may not be due to EIMD but due to the larger force production at longer fascicle lengths (40).…”
Section: Evidence From Human Studies For Eimd As a Hypertrophy Stimulusmentioning
confidence: 99%
“…When attempting to put this into the context of training with full versus partial ROM, it has been shown that training with a full ROM results in higher levels of muscle damage than training with partial ROM. 26 Therefore, it might be that training with a partial ROM may be more conducive for increases in muscle size when the training program is already designed to promote higher levels of muscle damage. This may indeed be the case if we consider that in the presence of muscle damage, increases in MPS may be directed more toward restoring this damage than to building the contractile protein pool.…”
Section: Upper Extremity Musculaturementioning
confidence: 99%
“…To determine the efficacy of a given resistance training program, it is paramount to measure the level of strength as accurately as possible. Furthermore, studies that explore the acute effects of resistance exercise on physiological parameters, such as muscle protein synthesis, hormonal responses, muscle soreness, electromyography outcomes, as well as studies on ergogenic effects of supplements, also use muscle strength testing as a basis for their respective exercise protocols [8][9][10][11][12][13]. Additionally, exercise prescription for repetition ranges in resistance training is also often based on a given percentage of maximal strength values [6], which further highlights the need for an accurate method of testing strength.…”
Section: Introductionmentioning
confidence: 99%